IMPLEMENTATION OF THE ISLAMIC TEACHERPRENEURSHIP CONCEPT IN THE MARKET DAY PROGRAM TO FORM THE CHARACTER OF MUSLIM ENTREPRENEURS. - Widarti, Tri; Kurniati, Edy Dwi; Ventura, Raghusfi Bhuena (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2025)
Instilling entrepreneurial character based on Islamic values is a challenge and urgent need in the world of Islamic education today. Teachers as central figures in education are expected to be able to play a role more than just teachers, namely as Islamic teacherpreneurs who are able to integrate sharia values into learning practices. This study aims to analyze the implementation of the Islamic Teacherpreneurship concept in the Market Day program and its role in shaping the character of Muslim entrepreneurs in students at the Khoiru Ummah Tahfidz Plus School, Semarang Regency. This study uses a descriptive qualitative approach with a case study method. Data collection techniques are carried out through participatory observation, semi-structured interviews, and documentation. Data analysis uses the Miles and Huberman interactive model. The results of the study show that teachers play an active role as facilitators and role models in instilling Islamic entrepreneurial values, such as honesty, trustworthiness, hard work, and usefulness. The Market Day program is run in a structured manner as part of character education based on real experiences. Students show positive developments in aspects of responsibility, independence, social empathy, and courage to take business initiatives. These findings confirm that the integration of Islamic Teacherpreneurship through Market Day activities is an effective approach in shaping the character of Muslim entrepreneurs holistically. This research provides conceptual and practical contributions to the development of a contextual and transformative Islamic education model. Keywords: Islamic Teacherpreneurship, Market Day, Muslim Entrepreneur Character, Islamic Education, Islamic Entrepreneurship